ANTI-HYPERGLYCEMIC EFFECT OF DIFFERENT FRACTIONS OF ANNONA RETICULATA LEAF - Rout, Soumya p; Kar, Durga m; Maharana, Laxmidhar (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT Context: Several species of the genus Annona were reported to have hypoglycemic properties and this makes Annona reticulata Linn. (Annonaceae) an interesting plant for investigating its anti-hyperglycemic potential. Objective: Different fractions prepared from hydro-alcoholic extract of A. reticulata leave were investigated for their blood glucose lowering effect on Streptozotocin (STZ) induced hyperglycemic rats. Methods: Ethyl acetate, methanol, and residual fractions (at dose level of 100 mg/kg by oral route) prepared from the hydro-alcoholic extract of A. reticulata leave were administered for 14 consecutive days to STZ induced hyperglycemic rats for evaluation of their anti-hyperglycemic potential. Anti-hyperglycemic potential was assessed by observation of a decrease in fasting blood glucose level. Results: The studies revealed that ethyl acetate fraction decreased the blood glucose level of hyperglycemic rats from 447.67 to 234.17 mg/dL and is significant (p<0.001) when compared with diabetic control group. The residual fraction and methanolic fraction decreased blood glucose level from 417.83 to 402.50 mg/dL and 432.33 to 371.67 mg/dL respectively but not significant when compared with the diabetic control group. Standard drug metformin (dose 300 mg/kg) reduced the blood glucose level from 447.33 to 219.50 mg/dL. Discussion: Ethyl acetate fraction at tested dose level was capable not only to control the elevated blood glucose level but also able to attenuate certain secondary parameters associated with STZ induced hyperglycemia. Conclusion: This study suggested that the ethyl acetate fraction prepared from hydro-alcoholic extract of A. reticulata leave exhibit potential antihyperglycemic property in the tested experimental models and should be investigated further. Keywords: Streptozotocin, Diabetes, Dyslipidemia.